High-performance self-driven broadband photoelectrochemical photodetector based on reduced graphene oxide/Bi2Te3 heterojunction - Chenchen Zhao; Yangyang Liu; Dongbo Wang; Wen He; Bingke Zhang; Jingwen Pan; Zhi Zeng; Donghao Liu; Sihang Liu; Shujie Jiao; Xuan Fang; Dan Fang; et al. (Nano Materials Science)
Attributed to its excellent physicochemical properties, graphene (GR) has very active applications in the fields of catalysis, optoelectronic devices, and battery electrode materials. However, until now, regulating the type and density of carriers in GR is still crucial for its practical applications. Here, reduced graphene oxide (RGO)-Bi2Te3 heterojunctions doped with different contents were prepared by a simple one-step method. The Bi2Te3 materials containing different RGO were made into broadband (365–850 ​nm) photoelectrochemical-type detectors, and the effects of the doping amount of RGO on the optoelectronic behavior of the devices and the intrinsic operation mechanism of the devices were investigated in detail. The results show that the values of Iph/Idark, Ri, and D∗ of Bi2Te3/RGO heterojunction devices obtained with 1 ​mg of RGO doping are 412, 6.072 ​mA/W, and 2.406 ​× ​1010 Jones, respectively. It is anticipated that this work will provide a research basis for future quantitative tuning of the performance of micro-nano devices by GR.